Life cycle assessment of wastewater treatment systems: Challenges and approaches - Hajar Abyar (Environmental Resources Research, 2022)
Water crisis and pollution increase have encouraged researchers to rehabilitate wastewater as an alternative water source. Wastewater treatment plants (WWTPs) implementation with high environmental and economic compatibility can be achieved using life cycle assessment (LCA). In this regard, the current review compared three well-known WWTPs including anaerobic/anoxic/aerobic (A2O), membrane bioreactor-reverse osmosis (MBR-RO), and integrated fixed-film activated sludge membrane bioreactor (IFAS-MBR) systems from an environmental perspective. The largest environmental impacts of the IFAS-MBR and MBR-RO were associated with climate change (27.5-95.13%) and human health (67.57-92%), while the midpoint and endpoint impacts of A2O were attributed to freshwater eutrophication (31.62%), marine ecotoxicity (29.94%), and resources (60.18%). The maximum and minimum energy consumption were observed in the A2O and MBR-RO configurations, respectively. The obtained results revealed that fossil fuels utilization remarkably influenced greenhouse gas (GHG) emission, specifically CO2. The sensitivity analysis also elucidated that electricity is the main indicator, which affected climate change (3.09-8%) and ozone depletion (18.97%) categories. Therefore, the results of the present study can be utilized as a guideline for further investigations in the LCA of various WWTPs.